Tomato chlorosis virus–encoded p22 suppresses auxin signalling to promote infection via interference with SKP1‐Cullin‐F‐boxTIR1 complex assembly. (16th June 2021) - Liu, Sijia; Wang, Cuilin; Liu, Xuedong; Navas‐Castillo, Jesús; Zang, Lianyi; Fan, Zaifeng; Zhu, Xiaoping; Zhou, Tao
Abstract: Phytohormone auxin plays a fundamental role in plant growth and defense against pathogens. However, how auxin signalling is regulated during virus infection in plants remains largely unknown. Auxin/indole‐3‐acetic acid (Aux/IAA) is the repressor of auxin signalling and can be recognized by an F‐box protein transport inhibitor response 1 (TIR1). Ubiquitination and degradation of Aux/IAA by SKP1‐Cullin‐F‐box TIR1 (SCF TIR1 ) complex can trigger auxin signalling. Here, with an emerging important plant virus worldwide, we showed that tomato chlorosis virus (ToCV) infection or stable transgenic overexpression of its p22 protein does not alter auxin accumulation level but significantly decreases the expression of auxin signalling–responsive genes, suggesting that p22 can attenuate host auxin signalling. Further, p22 could bind the C‐terminal of SKP1.1 and compete with TIR1 to interfere with the SCF TIR1 complex assembly, leading to a suppression of Aux/IAA degradation. Silencing and over‐expression assays suggested that both NbSKP1.1 and NbTIR1 suppress ToCV accumulation and disease symptoms. Altogether, ToCV p22 disrupts the auxin signalling through destabilizing SCF TIR1 by interacting with the C‐terminal of NbSKP1.1 to promote ToCV infection. Our findings uncovered a previously unknown molecular mechanism employed by a plant virus to manipulate SCF complex–mediated ubiquitin pathway and to reprogram auxin signalling for efficient infection. Abstract : Tomato chlorosis virus–encoded p22 protein can bind to the C‐terminal domain of SKP1 to interfere with the SCF TIR1 complex assembly, leading to suppressed auxin signalling and enhanced viral infection. Our findings unveil a new mechanism used by a plant virus to subvert ubiquitination to enhance infection.